Assessment Of Total Protein Concentration In Liver Of Fresh Water Fish, Channa Punctuates (Bloch.) With Special Reference To An Organophosphate Insecticide, Chlorpyrifos - FIRDOUS AHMAD MALLA (International Journal of Pharma and Bio Sciences, 2012)
Chlorpyrifos an organophosphate insecticide are being promoted world wid. on large scale day by day. Recently, a great deal of attention has been paid to evaluate the hazardous influence of an organophosphrous compound on physiology of many non-target organism, Particularly the fish. In the present study, the effect of an organophosphate insecticide (Chlorpyrifos) on total protein concentration in the liver of fish was assessed. Liver, being the main site of metabolism in the body of fish and is highly active in both toxifying and detoxifying foreign substance, was selected for the study. The determination of LC50 for chlorpyrifos insecticide was analyzed statistically by log dose/ probit regression line method (APHA, 1971). Fishes were exposed to 4 pm, 8ppm 12 ppm and control for 15 and 30 days, respectively. There was a significant (P<0.05) alterations between the control values and the exposed groups. The alteration in total protein concentrations was significantly, (P<0.05) dose dependent.